POLA ASUH ORANG TUA DALAM PERKEMBANGAN PERILAKU SOSIAL ANAK DI TAMAN KANAK –KANAK AISYIYAH BUSTANUL ATHFALKECAMATANTANETE RIATTANG KABUPATEN BONE - KURNIA, SELIA DWI (DIDAKTIKA, 2017)
This study examines the pattern of Parenting in the Development of Child Social Behavior in Kindergarten Aisyiyah Bustanul Athfal Tanete Riattang Sub-district Bone District. The problems statement of the research is: how is parenting pattern in the development of social behavior of children In Kindergarten Aisyiyah Bustanul Athfal Tanete Riattang Sub-district Bone District. The purpose of this research is to obtain data in depth about the condition of natural objects. The approach used in this research is descriptive qualitative, that is trying to know parenting pattern in the development of social behavior of child. The source of data in this research is 17 parents who are educated and educated in groups B (B1, B2, and B3) which are 17 children. Techniques of collecting data which are used in this research include observation, interviews, and documentation. The results of research are: parenting parenting is one of the things that affect the development of social behavior of children. The development of children's social behavior in the Aisyiyah Bustanul Athfal Kindergarten is characterized by the increasing cooperation of children, having the character of generosity, sympathy and selflessness.